MiRNA-378a as a key regulator of cardiovascular health following engineered nanomaterial inhalation exposure. Issue 5 (28th May 2019) - Hathaway, Quincy A.; Durr, Andrya J.; Shepherd, Danielle L.; Pinti, Mark V.; Brandebura, Ashley N.; Nichols, Cody E.; Kunovac, Amina; Goldsmith, William T.; Friend, Sherri A.; Abukabda, Alaeddin B.; Fink, Garrett K.; Nurkiewicz, Timothy R.; et al.
Abstract: Nano-titanium dioxide (nano-TiO2 ), though one of the most utilized and produced engineered nanomaterials (ENMs), diminishes cardiovascular function through dysregulation of metabolism and mitochondrial bioenergetics following inhalation exposure. The molecular mechanisms governing this cardiac dysfunction remain largely unknown. The purpose of this study was to elucidate molecular mediators that connect nano-TiO2 exposure with impaired cardiac function. Specifically, we were interested in the role of microRNA (miRNA) expression in the resulting dysfunction. Not only are miRNA global regulators of gene expression, but also miRNA-based therapeutics provide a realistic treatment modality. Wild type and MiRNA-378a knockout mice were exposed to nano-TiO2 with an aerodynamic diameter of 182 ± 1.70 nm and a mass concentration of 11.09 mg/m 3 for 4 h. Cardiac function, utilizing the Vevo 2100 Imaging System, electron transport chain complex activities, and mitochondrial respiration assessed cardiac and mitochondrial function. Immunoblotting and qPCR examined molecular targets of miRNA-378a. MiRNA-378a-3p expression was increased 48 h post inhalation exposure to nano-TiO2 . Knockout of miRNA-378a preserved cardiac function following exposure as revealed by preserved E/A ratio and E/SR ratio. In knockout animals, complex I, III, and IV activities (∼2- to 6-fold) and fatty acid respiration (∼5-fold) were significantly increased. MiRNA-378a regulated proteins involved in mitochondrial fusion, transcription, and fatty acid metabolism. MiRNA-378a-3p acts as a negative regulator of mitochondrial metabolic and biogenesis pathways. MiRNA-378a knockout animals provide a protective effect against nano-TiO2 inhalation exposure by altering mitochondrial structure and function. This is the first study to manipulate a miRNA to attenuate the effects of ENM exposure.